Signaling Pathways Tuning Innate Lymphoid Cell Response to Hepatocellular Carcinoma - Bourayou, Elsa; Golub, Rachel (Frontiers in Immunology, 2022)
Hepatocellular carcinoma (HCC) is one of the deadliest cancers worldwide and its incidence continues to rise globally. Various causes can lead to its development such as chronic viral infections causing hepatitis, cirrhosis or nonalcoholic steatohepatitis (NASH). The contribution of immune cells to HCC development and progression has been extensively studied when it comes to adaptive lymphocytes or myeloid populations. However, the role of the innate lymphoid cells (ILCs) is still under definition. ILCs are a family of lymphocytes comprising five subsets including circulating Natural Killer (NK) cells, ILC1s, ILC2s, ILC3s and lymphocytes tissue-inducer cells (LTi). Mostly located at epithelial surfaces, tissue-resident ILCs and NK cells can rapidly react to environmental changes to mount appropriate immune responses. Here, we provide an overview of their roles and actions in HCC with an emphasis on the importance of diverse signaling pathways (Notch, TGFb, Wnt/beta-catenin…) in the tuning of their response to HCC.